Children and participation in South Africa: Exploring the landscape - Rachel Bray; Sue Moses (Perspectives in Education, 2011)
Much of the literature on children’s participation distinguishes sharply between “informal” and “formal” forms of participation, which although analytically convenient, may limit possibilities for theorising. This paper examines tensions and links between children’s informal and formal participation, and looks at how participation is constituted in and by different social spaces in South Africa. Some of the ways in which children have participated in public matters prior to and following the advent of democracy in South Africa are examined, e.g. through public protest, school governance, law and policy development and service delivery. Shifts in the political landscape since apartheid are shown to have both opened and closed spaces and opportunities for children to influence decision making. Ultimately, a shrinking of informal spaces and the limited functioning of formal spaces due to popular attitudes and socio-economic factors has resulted in a constrained participation environment. Small shifts, however, in acknowledgement of the multiple ways that children collectively and individually contribute to the unfolding of everyday life, the emergence of new informal spaces and a broadening of the focus of participation initiatives, may herald an opportunity to move beyond often formulaic “formal” participation in governance to a broader inclusion of children in decision making.